Comparison of outcomes of monochorionic twin pregnancies conceived by assisted reproductive technology vs. spontaneous conceptions: A systematic review and meta-analysis - Wang, Minmin; Chai, Jingjing (Frontiers in Pediatrics, 2022)
Background: This review aimed to assess if monochorionic twin pregnancies conceived by assisted conception have worse maternal and neonatal outcomes as compared to those conceived naturally. Methods: Datasets of PubMed, ScienceDirect, CENTRAL, Embase, and Google Scholar were searched for studies comparing maternal and neonatal outcomes of monochorionic twin pregnancies conceived by assisted vs spontaneous methods. Results: Eight studies comparing 337 assisted with 2711 spontaneously conceived monochorionic twin pregnancies were included. Meta-analysis revealed that the mode of conception of monochorionic twin pregnancies had no impact on the risk of hypertensive disorders of pregnancy (HDP) (OR: 1.36 95% CI: 0.73, 2.54 I2=9% p=0.03), twin-twin transfusion syndrome (TTTS) (OR: 0.83 95% CI: 0.52, 1.31 I2=0% p=0.42), and very preterm delivery (OR: 1.18 95% CI: 0.74, 1.88 I2=41% p=0.49). We noted no statistically significant difference in the mean birth weights (MD: -17.66 95% CI: -157.23, 121.91 I2=82% p=0.80), risk of intra-uterine death (OR: 0.90 95% CI: 0.51, 1.60 I2=36% p=0.73) and small for gestational age between the two groups (OR: 0.92 95% CI: 0.67, 1.26 I2=0% p=0.59). There was an increased risk of caesarean sections (OR: 1.34 95% CI: 1.00, 1.80 I2=0% p=0.05) and neonatal death with assisted conceptions as compared to spontaneous conceptions (OR: 2.35 95% CI: 1.11, 5.01 I2=37% p=0.03). Conclusion: Monochorionic twin pregnancies conceived via assisted reproductive technology have a heightened risk of cesarean section and neonatal deaths. However, there is a need for further studies to supplement current evidence.